2022
DOI: 10.7150/thno.62708
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Tissue-derived Extracellular Vesicles for Osteoarthritis Theranostics

Abstract: Osteoarthritis (OA) is a prevalent chronic whole-joint disease characterized by low-grade systemic inflammation, degeneration of joint-related tissues such as articular cartilage, and alteration of bone structures that can eventually lead to disability. Emerging evidence has indicated that synovium or articular cartilage-secreted extracellular vesicles (EVs) contribute to OA pathogenesis and physiology, including transporting and enhancing the production of inflammatory mediators and cartilage degrading protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 227 publications
(233 reference statements)
0
50
0
Order By: Relevance
“…An increasing number of studies have shown that MSC has anti-apoptosis and cell proliferation-promoting effects ( 36 – 39 ). Apoptosis is divided into extrinsic (death receptor-mediated) and intrinsic (mitochondria-dependent) apoptotic pathways, which trigger the activation of downstream effector Caspase-3 through a series of signal transduction and ultimately initiate apoptosis ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that MSC has anti-apoptosis and cell proliferation-promoting effects ( 36 – 39 ). Apoptosis is divided into extrinsic (death receptor-mediated) and intrinsic (mitochondria-dependent) apoptotic pathways, which trigger the activation of downstream effector Caspase-3 through a series of signal transduction and ultimately initiate apoptosis ( 40 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to test this hypothesis, EVs were extracted from H1299 cells expressing different levels of AKR1B10 GFP (Low to High, see Supplementary Figure S1A for details), and levels of AKR1B10 in these EVs were estimated by Western blots (Figure 4A). Extraction by ultracentrifugation allowed for the sorting of EVs into two sub populations, the large EV, mainly composed of apoptotic bodies and microvesicles, and the Exosomes corresponding to small EVs with a diameter under 150 nm [33]. In order to test the possibility of the AKR1B10 GFP protein to be transferred between cell types, we exposed non-transfected RAW264.7 cells to EVs from H1299 cells, either expressing high levels of AKR1B10 GFP (H1299 High ) or without AKR1B10 GFP transfection (H1299 Ct ), and measured the GFP signal by FACS (Figure 4B).…”
Section: The Akr1b10 Protein Can Be Transferred Between Cell Types Vi...mentioning
confidence: 99%
“…The types of cells in the synovial fluid reflect the disease etiology, whether there is inflammatory arthropathy (sepsis, gout), or rheumatoid disease vs. an injury to the joint [ 113 ]. In RA, PEVs can leak into the synovial fluid, providing TF and a phospholipid surface on which the thrombin clot can form [ 57 , 134 , 152 , 154 ]. The PEVs that enter into the synovial fluid of RA patients contain more mitochondria and hyaluronan than the PEVs in osteoarthritis patients [ 35 , 155 ].…”
Section: Platelet-derived Extracellular Vesicles In Autoimmunitymentioning
confidence: 99%